Bacopaside II nanoparticles inhibit proliferation of C6 glioma cells - Vini C. Sekhar; Gayathri Viswanathan; Sabulal Baby (Elsevier, 2021)
Background: Bacopaside II is one of the four triterpenoid saponin components of bacoside A, the major bioactive constituent in the medicinal herb, Bacopa monnieri. Purpose: The present study is aimed to investigate the effect of PLGA-PEG encapsulated bacopaside II nanoparticles (BM1NPs) on C6 glioma cells. Methods: Bacopaside II was isolated from B. monnieri using sequential extraction followed by fractionation, column chromatography and characterized by FTIR and NMR. BM1NPs were prepared by nanoprecipitation and their physicochemical characterization was carried out by DLS, XRD, TEM and zeta potential analyses. Results: The spherical nanoparticles showed optimum size range, negative zeta potential and slow but significant in vitro release profile. BM1NPs (100-300 µg/mL) on MTT assay displayed 30-90% cell cytotoxicity against C6 glioma cells. In 2',7'-dichlorodihydrofluorescein diacetate (H2DCFDA) assay, BM1NP-treated cells showed more intracellular reactive oxygen species (ROS). The apoptosis-inducing property was evaluated by annexin V Alexa fluor 488 staining. EdU (5-ethynyl-2'-deoxyuridine) assay on C6 glioma cells confirmed the antiproliferative potential of BM1NPs. Cell cycle analysis by quantitation of DNA content showed the appearance of sub-G1 peak and confirmed the occurrence of apoptosis. Conclusion: Our results indicate that BM1NPs significantly inhibited C6 glioma cell proliferation and promoted cell apoptosis.